Awareness of colorectal cancer risk factor among students at Faculty of Medicine, Udayana University, Bali - huthayan Varmma Rajamanickam; Gede Eka Rusdi Antara (DiscoverSys Inc., 2019)
Introduction: Colorectal cancer is a major cause of morbidity and mortality throughout the world. To identify the presence of colorectal cancer, screening that is recommended can be carried out. Screening is an important process in every disease including colorectal cancer Method: This is crossectional-descriptive research. 100 samples that met inclusion criteria were included in the research. Samples obtained using consecutive sampling technique. The samples were interviewed to obtain the data used to fill out the questionnaireResult: 74% of the student has answered that a history of personal cancer are risk factors of colorectal cancer and also 88% of students have answered family history also a risk factor for colorectal cancer. The students have less knowledge on risk factors such as Inflammatory Bowel Disease (64%) and eating spicy food (60%). 87% of students agree that knowledge on colon and rectal cancer is important to prevent colorectal cancer.Conclusion: Good knowledge of colorectal cancer risk factors among students in medicine faculty, Udayana University.